IMPLEMENTASI FATWA MUI TENTANG OPERASI PERUBAHAN KELAMIN WARIA DAN PENYEMPURNAAN KELAMIN CACAT - La Jamaa; Faisal Kaliky (TAHKIM, 2022)
Reeality show, that there are people who are born with sex organs as a perfect man, but dressed as a woman, commonly called transvestites. Because there are psychiatric in question are not satisfied with its genitals. With advances in medical technology today, these conditions can be corrected through a sex change. In this context, Islam permits and even suggested a sex change for a person to have double genitalia, penis and vagina, or have no genitals at all (khunsa), to clarify and functioning optimally and definitively one of the genitals because it would provide a greater benefit compared with the hazard (mafsadat) it. While transsexual is a person of the opposite sex male genitals and physically perfect, but deliberately look or behave like a woman, the Indonesian Ulama Council (MUI) has issued a fatwa forbidden sex change operations for transsexuals.Keyword: Fatwa, transvestite, and gender operation